Pengembangan Permainan Sains Gelembung Salju Pelangi Berbasis Games untuk Meningkatkan Kemampuan Literasi Sains pada Pembelajaran Anak Usia Dini - Purwani, Dwi (Universitas PGRI Semarang, 2023)
The background that prompted this research was the unavailability of media that supports children in improving scientific literacy skills in early childhood. Teacher-centered learning so that students cannot describe objects in detail based on their observations, many children have very poor scientific literacy abilities, lack of children's interest in the learning provided by the teacher because the material provided does not activate students in the science learning process, the media used in less innovative learning. Teachers have not used games-based science games with IT media so that children's scientific literacy skills are low. This study aims to determine the effectiveness of using games-based rainbow snow bubble science game development to improve scientific literacy skills in early childhood learning. The approach used is research and development Research and development (R D). The approach and design used in this development research is using the ADDIE model. The research location was at TABITA Kindergarten, Ujungwatu, Donorojo sub-district, Jepara district. When the research was conducted in the even semester of the 2022/2023 school year. The subjects in this study were group B students aged 5-6 years. The sample used was 13 children. The data in this study were obtained through documentation, interviews, questionnaires, and pretest and posttest of children's expressive language skills. Data analysis techniques: Validation Test, Reliability, Practicality Test, Normality Test, Homogeneity Test and T Test. The results in the Game-Based Rainbow Snow Bubble Science Game Development research proved to be valid, effective, and practical to use to improve early childhood scientific literacy skills.